(E,E)-1-Methyl-2,6-distyrylpyridinium iodide - Penthala, Narsimha Reddy (International Union of Crystallography, 2010)
In the title compound, C(22)H(20)N(+)·I(−), the dihedral angles between the central pyridine ring and two outer benzene rings are 15.30 (10) and 11.82 (11)°. There are intermolecular π–π stacking interactions between the nearest phenyl ring over an inversion-related pyridyl ring, the shortest centroid–centroid distance being 3.672 (3) Å. The crystal structure of the compound indicates the 2,6-distyryl substituents have an E configuration.